Back Cover: Self‐assembled magnetic nanomaterials: Versatile theranostics nanoplatforms for cancer. Issue 2 (4th May 2021) - Wang, Shuren; Wang, Zhiyi; Hou, Yanglong
Abstract : Self‐assembled magnetic nanomaterials are a class of promising biomaterials developed by using self‐assembly synthesis technology. Their excellent physiochemical and biological characteristics make them have tremendous application potential in cancer theranostics. Combined with exogenous optical, acoustic and magnetic stimulation, self‐assembled magnetic nanomaterials can achieve the bioimaging‐guided cancer multimodal synergistic therapy through accessing into tumor tissues, eventually, leading to tumor ablation. (Article number 2021, 2, e18 )